2020
DOI: 10.1038/s41398-020-0833-7
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insula stimulation suppresses appetitive behavior while inducing forebrain activation in alcohol-preferring rats

Abstract: The anterior insular cortex plays a key role in the representation of interoceptive effects of drug and natural rewards and their integration with attention, executive function, and emotions, making it a potential target region for intervention to control appetitive behaviors. Here, we investigated the effects of chemogenetic stimulation or inhibition of the anterior insula on alcohol and sucrose consumption. Excitatory or inhibitory designer receptors (DREADDs) were expressed in the anterior insula of alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 69 publications
3
35
0
Order By: Relevance
“…When we challenged these animals by giving them CNO 60 min before the onset of the alcohol drinking sessions, we saw significant changes in alcohol consumption in animals expressing the DREADDs in all three brains areas. First, as a replication of our previously published data (Haaranen et al, 2020 ), CNO significantly altered alcohol intake in rats expressing Gq-DREADDs in the insula, as shown by a significant effect for session ( F (1,27) = 7.31, p = 0.012) and a significant session × vector interaction ( F (2,27) = 7.60, p = 0.002). A comparison of the CNO challenge sessions with the baseline sessions indicated that the 54% decrease in drinking produced by the Gq-DREADDs was significant ( t (9) = 4.00, p = 0.003), with no changes in the other CNO-challenged groups.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…When we challenged these animals by giving them CNO 60 min before the onset of the alcohol drinking sessions, we saw significant changes in alcohol consumption in animals expressing the DREADDs in all three brains areas. First, as a replication of our previously published data (Haaranen et al, 2020 ), CNO significantly altered alcohol intake in rats expressing Gq-DREADDs in the insula, as shown by a significant effect for session ( F (1,27) = 7.31, p = 0.012) and a significant session × vector interaction ( F (2,27) = 7.60, p = 0.002). A comparison of the CNO challenge sessions with the baseline sessions indicated that the 54% decrease in drinking produced by the Gq-DREADDs was significant ( t (9) = 4.00, p = 0.003), with no changes in the other CNO-challenged groups.…”
Section: Resultssupporting
confidence: 84%
“…In a replication of our previous study, we found that anterior insula stimulation by the Gq-DREADDs reduced alcohol consumption (Haaranen et al, 2020 ). The simple limited access alcohol drinking model does not allow us to analyze which aspects of drinking behavior were affected by insula stimulation apart from the consumed alcohol volume.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As with OFC, contributions of AI to alcohol seeking are complex and depend on a number of factors such as whether alcohol is presented in conjunction with a paired aversive outcome (Seif et al, 2013) or punishment-imposed abstinence (Campbell et al, 2019). Intriguingly, recent work has shown that chemogenetic inhibition of AI increases alcohol operant self-administration (Jaramillo et al, 2018a) and that chemogenetic activation of AI decreases alcohol (and sucrose) intake (Haaranen et al, 2020). Together these results show that, like OFC, AI is strongly involved in the use of alcohol and other reinforcers.…”
Section: Discussionmentioning
confidence: 99%